1986
DOI: 10.1002/dvg.1020070105
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genome modifications leading to genetic and epigenetic tumorous transformation in Nicotiana spp. tissue cultures

Abstract: A single system is presented, where both genetic and epigenetic control of tumor induction can be studied at the same time. This system is offered by the amphidiploid tumorous hybrid Nicotiana gluuca X N . langsdo@i, a nontumorous mutant of it and the nontumorous parent species N . glauca and N . langsdofii. The aim of the present paper is to compare long-term in vitro cultures of tumorous (genetic and habituated), and nontumorous strains, through the characterization of their genomes according to several phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, as shown in Table 5, the species whose tissues give rise to faster growing callus on minimal media are clearly concentrated in Petunioides. It is worth noting that habituation is known to be an epigenetically induced character possibly related to changes in methylation levels in key genes (Bogani et al, 1995;Durante et al, 1986), which may become stably heritable as a monogenic allele as shown by Meins (1989) (Baroncelli et al, 1974). This hypothesis is also supported by data in FIG.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, as shown in Table 5, the species whose tissues give rise to faster growing callus on minimal media are clearly concentrated in Petunioides. It is worth noting that habituation is known to be an epigenetically induced character possibly related to changes in methylation levels in key genes (Bogani et al, 1995;Durante et al, 1986), which may become stably heritable as a monogenic allele as shown by Meins (1989) (Baroncelli et al, 1974). This hypothesis is also supported by data in FIG.…”
Section: Discussionmentioning
confidence: 98%
“…Little is known about the identities of the genes involved in the early control of dedifferentiation. Since a high level of auxin is required to induce the formation of callus (1,13), it is likely that the expression of such genes, including possibly those coding for the mRNAs complementary to pNGSUB7 and pNGSUB8, is controlled at least in part by phytohormone levels. pNGSUB7 and pNGSUB8 appear to be derived from transcripts of two novel genes that are up-regulated early in dedifferentiation and to which we tentatively assign the names edeA and edeB respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth and in vitro culture Pith tissue was isolated from greenhouse-grown N.glauca. Some of this tissue was frozen immediately in liquid nitrogen; the remainder was cultured as described previously (13) and harvested after 4 h or 8 h of culture. At various times of culture, part of the tissue was transferred into liquid LS medium containing actinomycin D (2) and maintained for a further two weeks to check the effectiveness of the drug treatment.…”
Section: Methodsmentioning
confidence: 99%